2014
DOI: 10.1371/journal.pone.0109466
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetic Analyses of Helicobacter pylori Isolates from Gambian Adults and Children

Abstract: The gastric pathogen Helicobacter pylori is one of the most genetically diverse of bacterial species. Much of its diversity stems from frequent mutation and recombination, preferential transmission within families and local communities, and selection during persistent gastric mucosal infection. MLST of seven housekeeping genes had identified multiple distinct H. pylori populations, including three from Africa: hpNEAfrica, hpAfrica1 and hpAfrica2, which consists of three subpopulations (hspWAfrica, hspCAfrica a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Of the 40 isolated strains, 38 new sequence types are present, and two pairs of isolates have the same sequence type. A study by Secka et al (35) in Gombian showed that four pairs of sequence types were the same. Given that a pair of sequence types in the present study, which has the same sequence sequences, were isolated in different days of the patients and processed in the lab, thus most likely they reflect the transmission of completely related strains by unrelated members of the community.…”
Section: Discussionmentioning
confidence: 97%
“…Of the 40 isolated strains, 38 new sequence types are present, and two pairs of isolates have the same sequence type. A study by Secka et al (35) in Gombian showed that four pairs of sequence types were the same. Given that a pair of sequence types in the present study, which has the same sequence sequences, were isolated in different days of the patients and processed in the lab, thus most likely they reflect the transmission of completely related strains by unrelated members of the community.…”
Section: Discussionmentioning
confidence: 97%
“…Children who regularly swim in rivers, streams, and pools drink stream water, or eat uncooked vegetables are more likely to be infected [ 47 ]. H. pylori have been cultured from diarrheal stools of children in Gambia, West Africa, where almost all inhabitants are infected by five years of age [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…These genome sequences were initially selected based on published MLST data or based on the geographic location where the strains were isolated (Europe or West Africa). Six of the 8 strains of West African origin were originally isolated in The Gambia, and previous MLST analyses showed that most strains isolated in the Gambia are classified as hspWAfrica, based on MLST analysis [ 54 ].…”
Section: Methodsmentioning
confidence: 99%